2018
DOI: 10.1097/yco.0000000000000390
|View full text |Cite
|
Sign up to set email alerts
|

Adverse childhood experiences in children with autism spectrum disorder

Abstract: As bullying and other adverse experiences are common and associated with deleterious outcomes in children with ASD, there is a need for additional research on intervention strategies to prevent and mitigate the impact of these experiences. Ongoing work on the assessment of trauma experiences and PTSD symptoms in children on the spectrum is also needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
88
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(105 citation statements)
references
References 29 publications
2
88
0
4
Order By: Relevance
“…Overall, children with ASD‐only, ASD+ID, and ID‐only had significantly higher odds of reported and substantiated maltreatment relative to a population control group. With almost one in three children with ASD+ID reported to child protective services for maltreatment, and over one in five children with ASD‐only, these results bolster a growing literature emphasizing the importance of identifying and addressing maltreatment risk in ASD (Hoover, ; Hoover & Kaufman, ). Use of well‐established rigorous ADDM methodology that objectively identified a high number of children with ASD, and linkage with state‐wide child protective service records, may have allowed for identification of increased risk associated with ASD in contrast to prior work (e.g.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Overall, children with ASD‐only, ASD+ID, and ID‐only had significantly higher odds of reported and substantiated maltreatment relative to a population control group. With almost one in three children with ASD+ID reported to child protective services for maltreatment, and over one in five children with ASD‐only, these results bolster a growing literature emphasizing the importance of identifying and addressing maltreatment risk in ASD (Hoover, ; Hoover & Kaufman, ). Use of well‐established rigorous ADDM methodology that objectively identified a high number of children with ASD, and linkage with state‐wide child protective service records, may have allowed for identification of increased risk associated with ASD in contrast to prior work (e.g.…”
Section: Discussionmentioning
confidence: 70%
“…In summary, the current investigation represents the first empirical evidence from population‐level data that the prevalence of maltreatment is elevated in ASD relative to the general population. Establishing that children with ASD, who are already a population vulnerable to elevated family stress and emotional and behavioral difficulties, are also at heightened risk for maltreatment emphasizes the urgent need to consider developmental disability status in child maltreatment research and refine clinical supports for those doubly vulnerable families affected by both maltreatment and ASD and/or ID (Hoover & Kaufman, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Measures of Post-Traumatic Stress Disorder (PTSD) have rarely been included in studies of psychiatric co-morbidity in ASD and ID (Bakken et al, 2010). However, individuals with ASD and ID seem to be at increased risk of falling victim to violence (Sullivan & Knutson, 2000;Jones et al, 2012;Mandell, Walrath, Manteuffel, Sgro & Pinto-Martin, 2005;Duan et al, 2015), sexual abuse (Gotby et al, 2018;Hershkowitz, Lamb & Horowitz, 2007;Mandell et al, 2005;Sullivan & Knutson, 2000), maltreatment/neglect (Dinkler et al, 2017;McDonnell et al, 2018;Chan, Lo & Ip, 2018;Sullivan & Knutson, 2000;Turner, Vanderminden, Finkelhor, Hamby & Shattuck, 2011;Chan & Lam, 2016), and bullying (Hoover & Kaufman, 2018;Sullivan & Knutson, 2000;Hoover, 2015). McDonnell et al (2018) found that children with ASD and ID, or either of these conditions alone, were at increased risk of maltreatment.…”
Section: Introductionmentioning
confidence: 99%